Boosting gender equality through ADB trade finance partnerships. (Metro Manila, Philippines Asian Development Bank, 2018)
In the Asia and Pacific region, despite some progress, womens share in senior management in the public and private sectors is still poor. Unless impediments to womens labor force participation and promotion opportunities are removed, the region stands to lose considerably. Closing the gender gap in leadership leads to better business and financial outcomes. This study, cofunded by the Australian Department of Foreign Affairs and Trade, investigates how women are faring in the private banking sector and what can be done to promote their participation and leadership. It provides specific and practical recommendations to partner banks to advance the objective of attracting, retaining, and promoting more women in banking.
Keywords: Gender equality; Public-private sector cooperation -- Asia -- Finance; Electronic books